New EC quarterly on fisheries cooperation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
bilingual quarterly 'EC Fisheries Cooperation Bulletin/ CE Cooperation Peche'